Analisis Pemahaman dan Kepatuhan Wajib Pajak UMKM Tentang Kewajiban Perpajakan di Kecamatan Marpoyan Damai Pekanbaru - Ika Wulandari; Sahlia Rambe (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This study aims to determine and analyze understanding and compliance of taxpayers regarding tax obligations for SME’s in Marpoyan Damai District, Pekanbaru. The population in this study were 156 business owners and the data collection technique used was a questionnaire, the analysis prerequisite test used was the validity test and the reliability test. The results of the study show that the level of knowledge and understanding of taxpayers is categorized as good, for the level of compliance of taxpayers is categorized as sufficient while the ability of taxpayers to carry out their tax obligations is categorized as not good.Keywords:  Understanding of taxation, SME’s taxpayer Compliance, Tax Obligations